A method for constructing recruitment rules based on the analysis of a specialist’s competences - Lytvyn, Vasyl; Vysotska, Victoria; Pukach, Petro; Bobyk Іgor; Pakholok, Bohdan (Eastern-European Journal of Enterprise Technologies, 2016)
Under conditions of active development of innovative information technologies (IT) and eliminating the boundaries in providing educational services, human resources (staff, including IT specialists) turn into the main strategic resource of organizations, which ensures their long-term competitiveness and achievement of the set goals. Much emphasis in this problem is given to both the specific features of a recruiting company and to a high level of provision of educational services that meet international standards and requirements for the level of competences of would-be IT specialists. Therefore, the development of new conceptual approaches and promising information technologies of managing human resources acquires special relevance and practical significance. The article highlighted specific features of tasks of managing qualified human resources (MQHR), which allows identifying them as a task of multicriteria analysis and decision making in the fuzzy environment. A generalized conceptual model for decision making in the problems of MQHR was proposed. It was substantiated that in order to enhance effectiveness and transparency of decisions in MQHR, it is appropriate to use multicriteria optimizations based on the TOPSIS method, the advantages of which were shown. A modification of the algorithm for using TOPSIS for making recommendations in recruiting qualified human resources was proposed. The modification implies the integration of additional components of the content management in the decision making algorithm, which provides for the calculation based on the method of analysis of hierarchies (MAH) of coefficients of level or course of attained educational services. Using the TOPSIS and MAH methods and the scale of assessment of competence of qualified human resources, experimental calculations with ranking of alternatives were performed using the example of recruiting, which demonstrated effectiveness of the proposed approach.